1987
DOI: 10.1177/000456328702400304
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen and Progesterone Receptor Concentrations in Leiomyoma and Normal Myometrium

Abstract: SUMMARY. The content of cytoplasmic 17~oestradiol and progesterone receptors in human uterine leiomyoma and normal myometrium in the Negroid population was determined. Eighteen women of reproductive age. at various stages of the menstrual cycle. were included in the study. The serum oestrogen and progesterone concentrations were also measured. This is the first report in the literature in which oestrogen and progesterone receptors in leiomyoma are significantly higher than in normal myometrium (P=().()002). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 18 publications
2
23
0
3
Order By: Relevance
“…These tumors do not only morphologically resemble uterine leiomyomas, but they also are positive for ER, which is similar to uterine leiomyomas (21,22) and dissimilar to GISTs, which are ER-negative according to our results. Therefore, ER immunostaining is a valuable aid to separate the uterine type leiomyomas from GISTs.…”
Section: Discussionsupporting
confidence: 70%
“…These tumors do not only morphologically resemble uterine leiomyomas, but they also are positive for ER, which is similar to uterine leiomyomas (21,22) and dissimilar to GISTs, which are ER-negative according to our results. Therefore, ER immunostaining is a valuable aid to separate the uterine type leiomyomas from GISTs.…”
Section: Discussionsupporting
confidence: 70%
“…Strong evidence exists that the effect of estrogen is to increase the levels of both ER and PR in the myometrium, whereas the effect of progesterone is to decrease the level of the ER (Hsueh et al 1975;Katzenellenbogen 1980;Thi et al 1975). These conclusions are consistent with the sequential presentation of these two hormones during the menstrual cycle and the predominant observations that in the myometrium both ER and PR rise during the follicular (proliferative) phase and then fall during the luteal (secretory) phase of the menstrual cycle (Adams et al 1993;Buchi and Keller 1983;Englund et al 1998;Hsueh et al 1975;Janne et al 1975;Kawaguchi et al 1991;Lessl et al 1997;Marugo et al 1989;Rein et al 1990c;Sadan et al 1987;SchmidtGollwitzer et al 1979;Soules and McCarty 1982;Thi et al 1975). Because PR levels also fall during the luteal phase, some feel that progesterone may downregulate its own receptor (Englund et al 1998); this conclusion was also reached by Thi et al (1975), who demonstrated a fall in PR in the myometrium of ovariectomized guinea pigs when given progesterone (Thi et al 1975).…”
Section: Laboratory Studiessupporting
confidence: 75%
“…Interestingly, in one study (Marugo et al 1989) the ER and PR levels were significantly higher in submucous than subserosal leiomyomas, leading the authors to speculate about different etiologies and types of leiomyomas. The receptor concentrations were independent of the size of the tumor in one report (Sadan et al 1987). Another investigation found marked variation in ER and PR levels in different tumors from the same subject (Englund et al 1998); such heterogeneity may relate to the degree of hyalinization and involution of individual tumors.…”
Section: Laboratory Studiesmentioning
confidence: 87%
See 2 more Smart Citations